Improved results on state feedback stabilization for a networked control system with additive time-varying delay components' controller. (April 2018) - Zhang, Ruimei; Zeng, Deqiang; Liu, Xinzhi; Zhong, Shouming; Zhong, Qishui
Abstract: This paper investigates the problems of stability and stabilization for a networked control system (NCS) with additive time-varying delay components' controller. Firstly, stability of a NCS with additive time-varying delays is investigated. A novel approach with free parameters is proposed. By constructing a new Lyapunov-Krasovskii functional (LKF) with two free parameters, stability criteria are obtained. The obtained stability criteria depend not only on upper bounds of delays but also free parameters. In addition, input-output method is extended to study the stability problem for the NCS. Compared with other approaches such as input-output method, the free-parameter approach is more flexible and effective in reducing the conservatism. Then, based on the stability results, a state feedback controller is designed to guarantee the asymptotically stable of the closed-loop systems. Finally, numerical examples are provided to show the effectiveness and less conservatism of the proposed results. Highlights: A new LKF with two free parameters is constructed for NCSs. Specially, two free parameters τ 1 ∈ (0, h 1), τ 2 ∈ ( h 1, h ) are introduced in V 3 ( t ), V 4 ( t ), and V 5 ( t ), which can fully capture the information on the time-varying delays. Input-output method is extended to study the delay-dependent stability problem of NCSs. Compared with existing results in [14–18, 39 ], our results are more flexible and less conservative.